2020
DOI: 10.1101/2020.03.15.991844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

V367F mutation in SARS-CoV-2 spike RBD emerging during the early transmission phase enhances viral infectivity through increased human ACE2 receptor binding affinity

Abstract: 250 words 25 Importance: 150 words 26 Abstract 28 A novel coronavirus SARS-CoV-2 is associated with the current global pandemic of Coronavirus 29Disease 2019 . Spike protein receptor-binding domain (RBD) of SARS-CoV-2 is the 30 critical determinant of viral tropism and infectivity. To investigate whether the mutations in the RBD 31 have altered the receptor binding affinity and caused these strains more infectious, we performed 32 molecular dynamics simulations of the binding affinity between the mutant SARS-C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 47 publications
6
121
0
Order By: Relevance
“…For example, artefactual biases in mutational processes could confound signatures of mutational hotspots [28][29][30][31][32][33] . The issue of whether or not recombination has occurred during the outbreak is critical to the immunological battle against the virus and is under intense debate [6,[34][35][36][37][38][39][40] . Because many tests of recombination assume that all mutations can only occur once at each site, recurrent mutation and systematic errors can confound signatures of recombination [6,26,35] .…”
Section: Figure 1: Effect Of Recurrent Sequencing Mutations On Phylogmentioning
confidence: 99%
“…For example, artefactual biases in mutational processes could confound signatures of mutational hotspots [28][29][30][31][32][33] . The issue of whether or not recombination has occurred during the outbreak is critical to the immunological battle against the virus and is under intense debate [6,[34][35][36][37][38][39][40] . Because many tests of recombination assume that all mutations can only occur once at each site, recurrent mutation and systematic errors can confound signatures of recombination [6,26,35] .…”
Section: Figure 1: Effect Of Recurrent Sequencing Mutations On Phylogmentioning
confidence: 99%
“…A number of literature contributions now discuss the potential role for bats, pangolins, and other possible progenitor/intermediate species in derivation of SARS-CoV-2 from different approaches and perspectives, with a diversity of approaches and interpretations in understanding the origin of the virus. In particular, there has been extensive discussion and debate about the possible pangolin origin of SARS-CoV-2 (19,(21)(22)(23)(24)(25)(26)(27)(28)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). These studies provide useful insights into the evolution of SARS-CoV-2 but have limitations and uncertainty in drawing conclusions regarding the viral origin, as most studies were mainly performed through sequence-based comparison and simulation.…”
Section: Bat Virus Ratg13mentioning
confidence: 99%
“…They identified that the two groups of amino acid mutations in the SARS-CoV-2 RBD domain: the "similar affinity" group (F342L, R408I) and the "higher affinity" group (N354D D364Y, V367F, W436R). The "higher affinity" group RBD mutations under the positive selective pressure enhanced the infection efficiency of the SARS-CoV-2 [35]. Hence, epidemiology data and mutation surveillance are very important to reveal more exact spreading routes of the pandemic SARS-CoV-2.…”
Section: Rbd Mutations Enhance the Structure Stability And Infectivitymentioning
confidence: 99%